Management of Odontogenic Cutaneous Fistula Secondary to Dental Abscess: Report on Two Cases - Ni Putu Natasha Ayu Rupayasa; Nyoman Ayu Anggayanti; Ni Made Ista Prestiyanti (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Odontogenic cutaneous fistula is an abnormal pathway that causes pathologic communication between the cutaneous surface of the face skin and the oral cavity that occurs due to a chronic dental infection. Case: A 37-year-old male presented with frequent throbbing pain in all four wisdom teeth and a sunken scar on the lower left cheek, resulting from a carious lesion in the lower left molar. A 56-year-old female presented with a sunken scar on her cheek following the extraction of an infected upper molar. Case Management: Both odontogenic cutaneous fistulas were treated by addressing causative tooth infection, when present, in combination with fistulectomy. On follow-up, the first patient exhibited delayed wound closure, whereas the second achieved complete closure through a combined subcutaneous and cutaneous suturing technique. The extraoral fistula may present in various forms, with dimpling or retraction resulting from adherence to underlying tissues. Accurate diagnosis of odontogenic cutaneous fistulas that are often misdiagnosed require careful history taking, clinical evaluation, and radiographic examination. Definitive management typically involves fistulectomy to resolve the extraoral lesion. Conclusion: Odontogenic cutaneous fistulas are managed by eliminating dental infection and performing fistulectomy, with combined closure optimizing healing and aesthetic outcomes.